2013
DOI: 10.5606/ehc.2013.31
|View full text |Cite
|
Sign up to set email alerts
|

Artroskopik ön çapraz bağ onarımı için hamstring tendon otogreftine kıyasla kuadriseps tendon kullanımı: Klinik sonuçların karşılaştırmalı analizi

Abstract: Knee ligament injuries are among the most frequently encountered injuries. [1,2] Although different types of surgical techniques with excellent clinical results have been reported for the reconstruction of a ruptured anterior cruciate ligament (ACL), graft selection is still a controversial issue. Every particular graft type Amaç: Bu çalışmada, iki otojen greft türünün kullanımına ilişkin orta dönem klinik sonuçlar değerlendirildi. Hastalar ve yöntemler: Haziran 2005 -Kasım 2010 tarihleri arasında ameliyat edi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(3 citation statements)
references
References 16 publications
(16 reference statements)
1
2
0
Order By: Relevance
“…Controversial results have been reported about the best graft choice for ACL reconstruction when QT grafts and HT grafts were compared. A less residual laxity of QT graft was reported by Sofu et al, 11 and recent study have reported similar results between these autograft modalities using a cohort design 12 . In a previous randomised controlled trial we found that QT grafts had similar functional results with a better isokinetic ratio compared to HT grafts 13 …”
Section: Introductionsupporting
confidence: 69%
“…Controversial results have been reported about the best graft choice for ACL reconstruction when QT grafts and HT grafts were compared. A less residual laxity of QT graft was reported by Sofu et al, 11 and recent study have reported similar results between these autograft modalities using a cohort design 12 . In a previous randomised controlled trial we found that QT grafts had similar functional results with a better isokinetic ratio compared to HT grafts 13 …”
Section: Introductionsupporting
confidence: 69%
“…Both authors achieved comparable results to our study regarding knee stability at the time of follow up (QT graft at FU: instrumental measurement 1.1 ± 0.9 mm vs. 2.1 ± 1.9 mm vs. 1.6 ± 0.2 mm side-to-side difference; 93% vs. 67% vs. 80% negative pivot shift). Sofu et al did not achieve similar results [19]. In their study, 21% of QT graft recipients suffered from persistent symptoms of knee instability, and only 48% had side-to-side difference of < 3 mm.…”
Section: Discussionmentioning
confidence: 89%
“…Few previous studies have directly compared the clinical data of primary ACLR with QT grafts to that of ACLR with HT grafts, but the results are inconsistent (Table 5) [16–19].…”
Section: Discussionmentioning
confidence: 99%